Ethics in public relations and responsible advocacy theory - Haque, Md Shahidul; Ahmad, Jamilah (Penerbit UKM, 2017)
Ethics in public relations plays a vital role in human communication. It brings the credibility to organizations. It helps to establish faithful relationship between organizations and the public. Excellence in public relations can be achieved by ethical practices. Public relations organizations should follow code of ethics to provide reliable services to the target audience. Organizations need to ensure that the codes of ethics are practically implemented for the betterment of all the stakeholders. The responsible advocacy theory is one of the latest theories of ethics in public relations. It focuses on the responsibilities of public relations practitioners. It is based on three major principles of public relations ethics: the comparison of harms and benefits, respect of persons, and distributive justice. It encourages to avoid all harmful contents, guarantee the public interest, safeguard the human dignity and maintain justice in communication. This article highlights on the basic concepts of ethics in public relations, codes of ethics in different public relations organizations and key points of responsible advocacy theory.